Gage Bangbangtut: educational game innovation in Indonesian language learning in Islamic elementary school - Hamidulloh Ibda; Muhamad Arif; Nurma Febri Rakhmawati; Muhammad Nurul Iqbal (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This study aims to develop an educational game based on Temanggung local wisdom called Game Genially Bang Sindoro, Bang Sumbing, Tembakau Temanggungan (Gage Bangbangtut) as a learning medium to instill politeness in elementary school students. This game is designed by incorporating local cultural values relevant to the Temanggung community’s daily lives, so that students can learn to speak politely through contexts close to their environment. Research and Development (R&D) with the ADDIE model was applied as the research design to develop Gage Bangbangtut. The Gage Bangbangtut feature is designed with the Genially platform and can be installed on Windows. The content of Gage Bangbangtut contains the legend of Sindoro, Sumbing, and Temanggung Tobacco, Temanggung local wisdom (Names of Cultural Arts, Culinary Names, and District Names in Temanggung) in the form of games for students to play, and Temanggung’s distinctive language with two languages, namely Javanese and Indonesian, for grade 4 of the Islamic elementary school. The feasibility test results indicate that the mean score from game media expert validators is 0,97 (very high validity), from local wisdom expert validators is 0,68 (high validity), and from language politeness expert validators is 1,00 (very high validity). In addition, the results of the Gage Bangbangtut trial received a positive response from teachers and students and proved effective in improving the understanding of grade IV students about politeness in Indonesian language.